בין הנהר לים: ניתוח תרבותי ספרותי רב רובדי של שיר חתונה יהודי-ספרדי מהאי רודוס - הלד מיכל (מכאן, 2007)
This paper suggests a multi-disciplinary approach to a Judeo-Spanish folk song, traditionally performed during the ceremony of the bride’s purification bath before her wedding. The discussion focuses on the following issues: A description and analysis of the traditional ceremony (based on field work with elderly women who were born in the island of Rhodes. A presentation and analysis of the fictional and real characters related to the folk song. A description and analysis of the symbols that evolved in the folk song. A description and analysis of the reflexive system created around the folk song. An analysis of the status of the folk song in the context of the fact that the traditional Judeo-Spanish from which it sprung is disappearing at the point in time in which it was documented.